Parade's end [videorecording (DVD)] - Stoppard, Tom; White, Susanna; Richardson, Miranda; Everett, Rupert; Hall, Rebecca, 1982-; Cumberbatch, Benedict, 1976-; Clemens, Adelaide, 1989-; Ford, Ford Madox, 1873-1939 (Home Box Office, 2013)
An epic story of love and betrayal, set during a formative period in British history, from the twilight years of the Edwardian era to the end of World War I. Based on the quartet of novels by Ford Madox Ford, this five-part miniseries was adapted for the screen by Tom Stoppard.